Impact of Using Electro-pneumatic Training Kit on Improving Industrial Control System Skills of Vocational High School Students - Setyawan, Herlin; Sukardi, Sukardi; Rahayu, Wiwik; Risfendra, Risfendra; Jalinus, Nizwardi; Mardizal, Jonni (Universitas Ahmad Dahlan, 2025)
Practical learning using simulation applications makes students unable to create natural industrial control systems, so the impact of the immaturity of practical skills that students must master becomes a problem in this study. Using simulation applications, students are only faced with ideal conditions and symbols of each component, so students cannot know the actual components of an industrial control system and how to solve real problems in this system. This study aims to examine the impact of using electro-pneumatic training kits in an industrial control system practicum. The actual experimental research method used in the study consisted of an experimental class with 28 students and a control class of 25 people. Data collection techniques used skill assessment rubrics with data analysis techniques, including independent t-tests and effect sizes. The results revealed a significant difference in the skills of experimental class students with the control class, where experimental class students had better skills. From the results of the effect size test, it is known that the electro-pneumatic training kit significantly improves students' industrial control system skills. Based on these results, the electro-pneumatic training kit proved to be a transformational educational tool, significantly improving students' skills in industrial control systems. The implication of this study is for schools to integrate technology-based training tools such as electro-pneumatic training kits; vocational education can provide practical experience that is more relevant to industry needs, improve students' work readiness, and strengthen technical skills that are urgently needed in today's modern job market and industrial world.